Strategic Alumni Empowerment for Sustainable Development in Islamic Boarding School - Muhammad Fatichul Irsyad; Moh. Hanif Adzhar; Hairul Ma’arif; Sukron Makmun (at-Tahsin, 2026)
This study aims to thoroughly examine the strategic efforts in empowering alumni to develop the Islamic boarding school. Employing a qualitative approach with a case study design, data collection was carried out through semi-structured interviews, participatory observation, and document analysis. Data analysis followed an interactive model, encompassing data reduction, data presentation, and drawing conclusions, with the validity of the data ensured through source and technique triangulation. The results of the study reveal that alumni empowerment is carried out through strengthening the alumni organization, utilizing digital communication and networks, and involving alumni in education, economic, and socio-religious sectors. Alumni play a strategic role as partners of the boarding school in improving the quality of learning, enhancing social networks, and supporting institutional development. Furthermore, the research found that alumni have contributed significantly to the advancement of educational practices, with alumni-led initiatives positively impacting student engagement and curriculum enrichment. The study also indicates that the engagement of alumni in social-economic programs has facilitated the establishment of community-driven projects that promote the welfare of both the alumni and the surrounding community. Practically, it provides strategic recommendations to optimize the role of alumni sustainably. Future research could further explore the impact of alumni empowerment on long-term institutional sustainability and the broader socio-economic development of the Islamic boarding school community.